Breast Surgery Aesthetic Approaches (Springer International Publishing, 2018)
This book presents the latest and most essential techniques in Aesthetic Mastoplasty, an important field in plastic surgery that allows us to reshape breasts in harmony with the body's contours and with the patients' sense of beauty. Moreover, there have been major advances in this area in recent years, leading to improved and more tailored surgical outcomes. Breast surgeons should familiar with the most recent techniques in breast surgery, in order to provide a high standard of quality and patient-tailored surgical service. With these goals in mind, the book discusses the most important issues in the field, divided into four different sections: General Information for Breast Surgery, Surgical Principles of Breast Surgery, Breast Augmentation, and Liposuction and Lipoinjection. Written by a respected breast surgeon to honor the remarkable contributions of Prof. Ivo Pitanguy and featuring contributions from 39 Brazilian plastic surgeons, Breast Surgery - Aesthetic Approaches highlights the essentials and the latest advances developed by Brazilian plastic surgeons over the past 37 years. As such, it offers an invaluable practical surgical manual for all readers interested or working in breast surgery, including plastic and breast surgeons and plastic surgery residents.